Prognostic significance of cell surface phenotype in acute lymphoblastic leukemia - Aziz, Shiek Aejaz; Sharma, Susheel Kumar; Sabah, Iram; Jan, M Aleem (South Asian Journal of Cancer, 2015)
Context: To find out the phenotypic character of lymphoblasts of acute lymphoblastic leukemia (ALL) patients in our study cohort and their possible effect on the prognosis. Aims: To investigate the phenotype in ALL in our demographic population and to prognosticate various upfront current protocols employed in our hospital. Settings and Design: The study spanned over a period of 4 years with retrospective and prospective data of January 2008 through December 2011. Materials and Methods: 159 patients of all age groups were enrolled for the study, of which flow cytometry was done in 144 patients. Statistical Analysis Used: Analysis was done using the variables on SPSS (statistical package for social sciences) software on computer. Survival curves were estimated by method of Kaplan-Meir. Results: Majority of the patients were of B-cell (68.1%) and 30.6% patients were of T-cell lineage. Of these, 80.6% patients were having cALLa positivity. Complete remission (CR) was achieved in 59.1%, 16.4% relapsed, and 20.1% patients died. Conclusions: Phenotyping has become an important and integral part of diagnosis, classification, management and prognosticating in ALL. B-cell has been found to have a better survival over T-cell lymphoblastic leukemia. cALLa antigen positivity has good impact in achieving CR in only B-cell lineage, myeloid coexpression has no significant effect on the outcome. BFM (Berlin-Frankfurt-Münster) based protocols though showed a higher CR and survival vis-a-vis UKALL-XII. However, patients enrolled in former group being of low risk category and lesser in numbers cannot be compared statistically with a fair degree of confidence.
Keywords: Acute lymphoblastic leukemia; flow cytometry; immunophenotype; India; Kashmir; leukemia; phenotype; prognosis